Pengaruh Word of Mouth dan Brand Image Terhadap Keputusan Pembelian - Bilal Arfiansyah; Halimah Zahrah (Indo Publishing, 2026)
The increasingly tight competition in the automotive industry, especially in the dirt bike and supermoto segments, requires companies to understand the factors that influence consumer purchasing interest. This study aims to analyze the influence of Word of Mouth and Brand Image on Consumer Purchase Intention of Honda CRF 150 motorcycles in Bandung City, with a study on the Bandung Supermoto Community. The research method used is a quantitative approach with descriptive and verification research types. Data collection techniques were carried out by distributing questionnaires to respondents who met the research criteria. The data obtained were analyzed using multiple linear regression analysis, t-test, F-test, and coefficient of determination. The results of the study indicate that Word of Mouth has a positive and significant effect on Purchase Intention, as well as Brand Image has a positive and significant effect on Purchase Intention. Simultaneously, Word of Mouth and Brand Image have a significant effect on Consumer Purchase Intention. These findings indicate that positive communication between consumers and a strong brand image play an important role in increasing purchase interest in the Honda CRF 150 motorcycle.